Kryteria decyzyjne a strategie inwestycyjne przedsiębiorstw - Siewiera, Agnieszka (Criteria of Decision-making and Company's Investment Strategies, 2007)
Companies are under constant influence of the market, forcing them to adapt to its ongoing changes. A company has to treat this situation not as a threat, but as a chance to undertake new challenges. Successful company cooperates closely with its environment, cares about customers' needs and quality and competitiveness of its products. Strategic planning, including investment strategic, is based on recognizing the market environment and the company needs. To fulfill the conditions of reasonable investment, investments have to be subject to strategic aims of the company. Aims defined by company's global strategy, requiring investments, become company's investment aims. For a company investment decisions are the most crucial, because a long-term engagement of company's capital is connected with high risk, which should be evaluated by investors. From the economic point of view, any investment is worth to undertake, if only it guarantees achievement of anticipated results. Every party engaged in the project expects it to bring certain profits, but they may use different criteria to evaluate those profits and the project itself. Every investment is a part of socioeconomical system, and realization of a project may also depend on the degree to witch it will contribute to the public interest. Project, as a part of supply and demand market system, is successful when it ensures the most effective use of limited resources.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 491-497